Islamic Counselling and Spiritual Recovery: A Case Study at Medan Plus Rehabilitation Foundation - Mhd Arifin; Zulkarnain Abdurrahman (Journal of Mathematics Instruction, Social Research and Opinion, 2025)
Drug abuse in Indonesia leads to multidimensional impacts that not only damage physical and psychological health but also diminish the spiritual and moral quality of individuals. Therefore, the rehabilitation of drug addicts needs to integrate spiritual aspects in addition to medical and psychological aspects. This research examines the role of Islamic counselling in restoring the spirituality of victims of drug abuse at the Medan Plus Rehabilitation Foundation in Medan. The research method uses a descriptive qualitative approach with data collection techniques consisting of in-depth interviews and participatory observations of six participants, including the head coordinator, Islamic counsellors, and victims of drug abuse. Data analysis is conducted thematically manually with data source triangulation to ensure the credibility of the results. The findings indicate that implementing Islamic counselling through worship guidance, group therapy, and the reinforcement of Islamic values is effective in rebuilding spirituality, enhancing motivation, and strengthening the mental resilience of rehabilitation participants. The personal and collaborative approach between counsellors and foundation staff successfully addressed participants' openness barriers and information limitations. Regular spiritual activities such as dhikr, reading the Qur'an, and nightly evaluations provide a conducive atmosphere for comprehensive recovery and social reintegration. This research contributes to developing religion-based rehabilitation models in Indonesia, particularly those that integrate Islamic values holistically and measurably.